Board Members' Performance Achievements In Development In Barat Aceh District - Manan, Afni Abdul (International Journal of Ethno-Sciences and Education Research, 2021)
Regional autonomos originated from the demands of  Indonesian society since the reform era in 1998. This is one of the community's requirements to carry out development. In accordance with the rules of the autonomous legislation law number  32 of 2004 about local goverment and number 33 of 2004. Governments in the regions that are allowed to manage their regions are the council. In order to fulfill  the need of community’s development, the council has a big  role that need to be implemented. The development of community in Aceh Barat is still below standard, especially in the field of human capital. This is because Aceh Barat experienced a tsunami in 2004 and causing a lot of damage in infrastructure chain. The role of the council is needed to take care of its territory in supervision and finance. Both of the roles need to be assessed by the headman to get an optimal impact. This study used qualitative methods and descriptive analysis. The data is obtained through interviews and observations. A total of nine respondents were selected to provide information in this study. The three area in this study were Arongan Lambalek, Tanjong, and West Woyla. The study showed that the role of the council is indispensable for development. The intended role is the role of financial transactions and supervision that influence development in various aspects. Therefore, two-way communication between the council and the community is needed. Another alternative of the headman is required to achieve the community's development goals. The result of the study also showed a good relationship between the council and the headman in the process of development implementation. This showed that the council worked optimally to develop its territory as community desires. The assistance provided by the council is not the same because each regions is different from the others. The factors that affected the role of the council are the factors of experience and knowledge. The result of this study formulated the majority of the council have played its role namely the role of finance and supervision. And so on, the majority of the headman provide a good perspective to the role of the council in the development of community in Aceh Barat.